2022
DOI: 10.1002/jsfa.12038
|View full text |Cite
|
Sign up to set email alerts
|

Emulsifying and whipping properties of mixing polysaccharide dispersions: effect of ratio between insoluble soybean fiber and hydroxypropyl methylcellulose

Abstract: BACKGROUND The interactions between various food colloids in different systems (e.g., dispersions, emulsions, creams) have a bearing on the processing and characteristics of food systems. Hydrophilic polysaccharides have been proven to have the potential to fabricate the above systems. In the present work, hydroxypropyl methylcellulose (HPMC) was partially replaced by the insoluble soybean fiber (ISF) extracted from defatted okara to prepare mixing dispersions, oil‐in‐water emulsions and whipped creams. RESULT… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…2,3 Soybean fiber is the main component of okara, and some researches have proved that insoluble soybean fiber (ISF) can be alone used as a particulate stabilizer for oil in water Pickering emulsions 4,5 and also can stabilize emulsions with other emulsifiers. 6,7 For instance, ISF extracted by homogenization combined with alkaline treatment could produce stable Pickering emulsions and high-intensity homogenization effectively inhibiting creaming in ISF-emulsions. 4 It has been found that physical treatment could cause changes in the structure and physicochemical properties of soybean dietary fiber, 8,9 while more research is needed to be focused on the ISF from okara.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…2,3 Soybean fiber is the main component of okara, and some researches have proved that insoluble soybean fiber (ISF) can be alone used as a particulate stabilizer for oil in water Pickering emulsions 4,5 and also can stabilize emulsions with other emulsifiers. 6,7 For instance, ISF extracted by homogenization combined with alkaline treatment could produce stable Pickering emulsions and high-intensity homogenization effectively inhibiting creaming in ISF-emulsions. 4 It has been found that physical treatment could cause changes in the structure and physicochemical properties of soybean dietary fiber, 8,9 while more research is needed to be focused on the ISF from okara.…”
Section: Introductionmentioning
confidence: 99%
“…Quantities of okara are produced around the world, which is still in low utilization and has attracted growing attention 2,3 . Soybean fiber is the main component of okara, and some researches have proved that insoluble soybean fiber (ISF) can be alone used as a particulate stabilizer for oil in water Pickering emulsions 4,5 and also can stabilize emulsions with other emulsifiers 6,7 . For instance, ISF extracted by homogenization combined with alkaline treatment could produce stable Pickering emulsions and high‐intensity homogenization effectively inhibiting creaming in ISF‐emulsions 4 .…”
Section: Introductionmentioning
confidence: 99%